Robert G. Spivack papers - Spivack, Robert G.
Correspondence, articles, book projects, columns, newsletters, newspapers, material relating to speaking engagements, topical files, records of organizations, scrapbooks, printed matter, and other papers relating chiefly to Spivack's career as a newspaper reporter with the New York Post, syndicated columnist, and newletter publisher. Includes Spivack's articles published in the New York Post; his newspaper columns, "Town's Backrooms" and "Watch on the Potomac"; and his newsletters, Private Wire and Spivack Report. Subjects include national politics including the Dwight D. Eisenhower and Lyndon B. Johnson presidential administrations, New York State politics, and New York City politics, especially the connections between organized crime and politics. Includes materials pertaining to Spivack's work as editor of the University of Cincinnati newspaper, Cincinnati Bearcat; the Reporters' News Syndicate, his program designed to train minorities in journalism; and his participation in student groups such as Student Defenders of Democracy, International Student Service, and Fight For Freedom as well as other organizations advocating for war refugees, against American isolationism, and seeking the intervention of the United States in World War II prior to the Pearl Harbor attack. Individuals represented include Owen Brewster, Frank Costello, Thomas E. Dewey, Jonah J. Goldstein, Irvin McNeil Ives, Joseph McCarthy, Newbold Morris, William O'Dwyer, and Franklin D. Roosevelt.
Correspondents include Herbert Agar, Wilbur E. Bade, Ulric Bell, George T. Bye, Elliott E. Cohen, Louis G. Cowan, Fern Marja Eckman, Lloyd D. Hagan, Joseph P. Lash, Reuben A. Lazarus, Newbold Morris, Herbert Nagourney, Shaemas O'Sheel, Oliver Pilat, Eleanor Roosevelt, Arthur J. Rosenthal, Paul Sann, Dorothy Schiff, John Herman Henry Sengstacke, Eric Sevareid, Abraham M. Sirkin, Martin Sommers, Mark Starr, Rex Stout, and James A. Wechsler.
Journalist. Full name: Robert Gerald Spivack. Born, 1915. Died, 1970.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Agar, Herbert, -- 1897-1980 -- Correspondence; Bade, Wilbur E. -- 1906-1954 -- Correspondence; Bell, Ulric, -- 1891-1960 -- Correspondence; Brewster, Owen, -- 1888-1961.; Bye, George T. -- Correspondence; Cohen, Elliot E., -- 1899-1959 -- Correspondence; Costello, Frank, -- 1891-1973.; Cowan, Louis G., -- 1909-1976 -- Correspondence; Dewey, Thomas E. -- 1902-1971.; Eckman, Fern Marja -- Correspondence; Eisenhower, Dwight D. -- 1890-1969.; Goldstein, Jonah J., -- 1886-1967.; Hagan, Lloyd D. -- Correspondence; Ives, Irving McNeil, -- 1896-1962.; Johnson, Lyndon B. -- 1908-1973.; Lash, Joseph P., -- 1909-1987 -- Correspondence; Lazarus, Reuben A. -- 1895-1971 -- Correspondence; McCarthy, Joseph, -- 1908-1957 -- Correspondence; Morris, Newbold; Morris, Newbold -- Correspondence; Nagourney, Herbert -- Correspondence; O'Dwyer, William, -- 1890-1964.; O'Sheel, Shaemas, -- 1886-1954 -- Correspondence; Pilat, Oliver, -- 1903-1987 -- Correspondence; Roosevelt, Eleanor, -- 1884-1962 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945.; Rosenthal, Arthur J. -- 1919-2013 -- Correspondence; Sann, Paul -- Correspondence; Schiff, Dorothy, -- 1903-1989 -- Correspondence; Sengstacke, John Herman Henry, -- 1912-1997 -- Correspondence; Sevareid, Eric, -- 1912-1992 -- Correspondence; Sirkin, Abraham M. -- Correspondence; Sommers, Martin -- Correspondence; Starr, Mark, -- 1894- -- Correspondence; Stout, Rex, -- 1886-1975 -- Correspondence; Wechsler, James A. -- 1915-1983 -- Correspondence; Fight for Freedom (Organization); International Student Service; University of Cincinnati; Cincinnati bearcat; New York post; Private wire; Spivack report; Isolationism -- United States; Journalism -- United States; Minorities in journalism -- United States; Students -- Political activity -- United States; World War, 1939-1945.; World War, 1939-1945 -- United States; World War, 1939-1945 -- Refugees; New York (N.Y.) -- Politics and government -- 20th century; New York (State) -- Politics and government -- 20th century; United States -- Politics and government -- 20th century; Journalists